FINANCIAL ALLOCATION FOR SUSTAINABLE LANDFILL MANAGEMENT IN UZBEKISTAN - Sarvarbek, Shomurodov; Gautama, Budhi Pamungkas; Hendrayati, Heny; Qudratov, Inomjon (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
This study analyzes how financial resources should be allocated in Uzbekistan’s landfill-based municipal solid waste system to improve ecological performance and economic sustainability. The article is adapted from the author’s original IMRAD manuscript and reorganized to match the Abisatya Eko-Bisma journal template . The study uses documentary analysis, comparative literature review, scenario modeling , and multi-criteria assessment to compare four allocation strategies: business-as-usual, landfill-first, circular-recovery, and an integrated hybrid model . The results show that simply spending money on disposal sites won't make landfills work better. Putting together a financing package that includes all of the following is the best way to do this: better collection , better transfer logistics , clean landfills , controlling methane and leachate, digital billing , and slowly recovering materials . Putting landfills first makes it easier to follow the rules , but it doesn't work as well for circularity and getting money back over time . It's hard to put a model that relies heavily on recycling into action if collection reliability and engineered disposal capacity aren't always reliable . A hybrid allocation model that is backed by tariff reform, better data systems, extended producer responsibility , and climate-linked financing is the best way to go . The research shows that Uzbekistan can move from a system where people only use landfills when they need to to a public utility model. This model is more stable, protects the environment, makes services more reliable, and helps the economy move to a more circular model .